YouTube Usage in the University Classroom: An Argument for its Pedagogical Benefits - Jackman, W. Marc (International journal of emerging technologies in learning, 2019)
The demands of teaching at the tertiary level are increasing all the time. YouTube is one of the new e-resources that can be used in contemporary tertiary education pedagogy. This paper is an account of YouTube usage in three psychology classes (adolescent, developmental, and educational psychology) at the University of Trinidad and Tobago. This paper reports on the usage of YouTube videos as means of summarising course content, clarifying complex concepts, concretising abstract ideas, modelling appropriate interventions, reinforcing domain-specific jargon, exploring vicarious laboratory experimentation, and capturing first-hand musings and expositions of historical and contemporary theorists in the field of psychology. A rationale for each particular use was also given as well as the real and potential benefits to modern students.